2023
DOI: 10.3390/nu15041025
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Breakfast Consumption of Medium-Quantity and High-Quality Food Choices Is Associated with Better Vascular Health in Individuals with Cardiovascular Disease Risk Factors

Abstract: Background: Breakfast consumption has been associated with the improvement of many cardiovascular disease (CVD) risk factors, yet data regarding its association with subclinical vascular damage, which precedes the onset of CVD, are scarce. The aim of this study is to investigate this association in a large sample of adults with CVD risk factors. Methods: Anthropometric measurements, vascular biomarkers and dietary intake with two 24-h dietary recalls, focusing on breakfast frequency and its quantity and conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…A good breakfast provides important nutrients from macronutrients for children's growth and development, including fiber, potassium, calcium, vitamins C and D, folate, iron, zinc and magnesium which contribute an average of around 474 kcal of energy 39,47 . Moreover, a good breakfast was able to control blood glucose levels, fulfill daily intake earlier, prevent overweight and obesity and reduce the risk of other metabolic diseases 41,44,[48][49][50] . A good breakfast pattern includes various aspects to ensure children get adequate nutrition, the energy they need, and have healthy eating habits [40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…A good breakfast provides important nutrients from macronutrients for children's growth and development, including fiber, potassium, calcium, vitamins C and D, folate, iron, zinc and magnesium which contribute an average of around 474 kcal of energy 39,47 . Moreover, a good breakfast was able to control blood glucose levels, fulfill daily intake earlier, prevent overweight and obesity and reduce the risk of other metabolic diseases 41,44,[48][49][50] . A good breakfast pattern includes various aspects to ensure children get adequate nutrition, the energy they need, and have healthy eating habits [40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…The Breakfast Quality Index (BQI) is a tool for assessing the nutritional quality of breakfast in epidemiological studies [ 16 ], based on the food groups and nutrients intake with the rationale of O’Neil, 2014 [ 15 ] and the scoring system proposed by Monteagudo, 2013 [ 14 ]. In adults, an overall good breakfast quality has been associated with a healthier cardiometabolic profile independent of overall diet quality [ 17 , 18 ] and with the achievement of daily nutrient requirements [ 9 , 16 ]. Observational studies of breakfast consumption in association with mental health are also emerging [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the remarkable contribution of genetic factors in the pathogenesis of T2DM is well established, the constant incidence increase in diabetic patients targets focal attention on environmental determinants like modifiable risk factors, such as obesity, physical inactivity, and dietary habits. Epidemiological studies reported that adequate dairy intake may lower the incidence of cardiovascular diseases, underlining that acting on modifiable risk factors for T2DM development could be effective in the prevention of disease [ 15 , 16 , 17 ]. To this aim, the search for nutrients and food-derived compounds able to modulate age-related epigenetic mechanisms promoting beneficial/preventive effects still represents an open field.…”
Section: Introductionmentioning
confidence: 99%